(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In the study of political, economic, social and cultural processes in the history of our nation, historical sources and literature play an important role in restoring historical reality. When we talk about the religious policy carried out in our country during the Soviet government, the persecutions in this area, the softening of the relations between the country and religion during the years of the Great Patriotic War in the labors of the Soviet government, first of all, depending on the decisions made by the Central Committee of the CPSU and the USSR Council of Ministers We are witnessing that the features of atheistic propaganda are highlighted in various regions of the USSR.